2020
DOI: 10.11648/j.rs.20200502.11
|View full text |Cite
|
Sign up to set email alerts
|

Level of Self-care Practice and Associated Factors Among Hypertensive Patients in Jimma University Specialized Hospital, South West Ethiopia

Abstract: Globally hypertension is a major public health problem and leading cause of mortality in developing countries. Self-care practice encourage hypertensive patients to have better quality of life by preventing complication and decrease health care expenditure. The aim of this study is to assess Self-care practice and associated factors among hypertension patients in Jimma university specialized hospital, south west Ethiopia. An institution based Cross sectional study was employed on 322 adult hypertensive patient… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
4
8
0
Order By: Relevance
“…Meanwhile, low SCB levels in hypertension patients with comorbidities could worsen their conditions. 27 This result is supported by a previous study, which found the history of comorbidities to be significantly associated with SCB when implementing lifestyle modification practices. 28 Therefore, hypertension accompanied by comorbidities is complicated to control.…”
Section: Discussionsupporting
confidence: 74%
“…Meanwhile, low SCB levels in hypertension patients with comorbidities could worsen their conditions. 27 This result is supported by a previous study, which found the history of comorbidities to be significantly associated with SCB when implementing lifestyle modification practices. 28 Therefore, hypertension accompanied by comorbidities is complicated to control.…”
Section: Discussionsupporting
confidence: 74%
“…is study revealed that the odds of age greater than or equal to 65 years had 3.8 times more likely to have good selfcare practice compared to age less than 40 years. is was supported by the study done in Harar town [16] and in Jima [21]. e study done in North Ethiopia Tigray; hypertension patients with the age of greater than or equal to 65 years were 3.2 times more likely to adapt to good self-care practice towards hypertension than those above the age of 65 years [12].…”
Section: Discussionmentioning
confidence: 84%
“…The sample size was determined by using a single population proportion formula by taking 44.7% proportion from previous study and assuming 5% marginal error, 95% confidence interval and 5% nonresponse, and the final sample size was 399 [ 21 ]. Systematic sampling technique was used to recruit study participants, and every other patient who came for follow-up in the hypertension chronic outpatient clinic was interviewed.…”
Section: Methodsmentioning
confidence: 99%
“…The included studies were reported from five regions and one city administration of the country. Four studies were reported from the Oromia regional state [ 28 , 34 , 36 , 37 ]. Three studies were from Amhara regional state [ 38 40 ], three studies from Harari regional state [ 35 , 41 , 42 ], three studies from Addis Ababa city administration [ 43 45 ], two studies from Tigray regional state [ 27 , 46 ], and two studies from South Nations Nationalities and Peoples Regional State (SNNPR) [ 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The current study identified two predictors, namely, knowledge about hypertension and the educational status of hypertensive patients. The analysis of nine cross-sectional studies [ 27 , 35 , 37 , 39 , 41 , 43 , 44 , 47 , 48 ] showed that the educational status of the hypertensive patients was significantly associated with hypertensive self-care practice. Hypertensive patients who attended formal education were approximately 3 times more likely to adhere to hypertensive self-care practice than those who did not attend formal education (AOR = 2.82; 95% CI 2.18, 3.64) ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%